Association between patient race and staff resuscitation efforts after cardiac arrest in outpatient dialysis clinics: A study from the CARES surveillance group. (November 2020) - Hofacker, Samuel A.; Dupre, Matthew E.; Vellano, Kimberly; McNally, Bryan; Starks, Monique Anderson; Wolf, Myles; Svetkey, Laura P.; Pun, Patrick H.
Abstract: Background: Cardiac arrest is the leading cause of death among patients receiving hemodialysis. Despite guidelines recommending CPR training and AED presence in dialysis clinics, rates of CPR and AED use by dialysis staff are suboptimal. Given that racial disparities exist in bystander CPR administration in non-healthcare settings, we examined the relationship between patient race/ethnicity and staff-initiated CPR and AED application within dialysis clinics. Methods: We analyzed data prospectively collected in the Cardiac Arrest Registry to Enhance Survival across the U.S. from 2013 to 2017 and the Centers for Medicare & Medicaid Services dialysis facility database to identify outpatient dialysis clinic cardiac arrest events. Using multivariable logistic regression models, we examined relationships between patient race/ethnicity and dialysis staff-initiated CPR and AED application. Results: We identified 1568 cardiac arrests occurring in 809 hemodialysis clinics. The racial/ethnic composition of patients was 31.3% white, 32.9% Black, 10.7% Hispanic/Latinx, 2.7% Asian, and 22.5% other/unknown. Overall, 88.0% of patients received CPR initiated by dialysis staff, but rates differed by race: 91% of white patients, 85% of black patients, and 77% of Asian patients (p = 0.005). After adjusting for differences in patient and clinic characteristics, black (OR = 0.41, 95% CI 0.25–0.68) and Asian patients (OR = 0.28, 95% CI 0.12–0.65) were significantly less likely than white patients to receive staff-initiated CPR. No significant difference between staff-initiated CPR rates among white, Hispanic/Latinx, and other/unknown patients was observed. An AED was applied by dialysis staff in 62% of patients. In adjusted models, there was no relationship between patient race/ethnicity and staff AED application. Conclusions: Black and Asian patients are significantly less likely than white patients to receive CPR from dialysis staff. Further understanding of practices in dialysis clinics and increased awareness of this disparity are necessary to improve resuscitation practices.